2017
DOI: 10.26496/bjz.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an experimental resource pulse on the macrofaunal assemblage inhabiting seagrass macrophytodetritus

Abstract: ABSTRACT. Physical disturbances and resource pulses are major structuring drivers of terrestrial and aquatic ecosystems. The accumulations of exported dead leaves from the Neptune grass, Posidonia oceanica (L.) Delile are ephemeral and highly dynamic detrital habitats offering food sources and shelter for vagile macrofauna community. These habitats are frequently subject to wind and storms which can add "new" detrital material to previous accumulations; these can be defined as resource pulses and could potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…epiphytic and microbial biomass) (Mascart et al, 2015b), but also quality (detritus ageing, enrichment by microbial biomass, fatty acid composition), are probably the main drivers of trophic competition and trophic niche partitioning between these two eco-morphotypes, tightly associated to phytal habitats. These resource pulses have been demonstrated to have an important effect on macrofauna biodiversity in studied EMAs (Remy et al, 2017).…”
Section: Do Copepod Trophic Ecology Vary Seasonally?mentioning
confidence: 99%
See 1 more Smart Citation
“…epiphytic and microbial biomass) (Mascart et al, 2015b), but also quality (detritus ageing, enrichment by microbial biomass, fatty acid composition), are probably the main drivers of trophic competition and trophic niche partitioning between these two eco-morphotypes, tightly associated to phytal habitats. These resource pulses have been demonstrated to have an important effect on macrofauna biodiversity in studied EMAs (Remy et al, 2017).…”
Section: Do Copepod Trophic Ecology Vary Seasonally?mentioning
confidence: 99%
“…In addition, EMAs are seasonally pulse-sourced by dead seagrass leaves and the epiphytic community covering them (Mascart et al, 2015b;Remy et al, 2017). Therefore, food item availability fluctuates over time, and this could have consequences for copepod trophic ecology and food partitioning between the different copepod ecomorphotypes (Mascart et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…The extreme abundance of this resource, despite poor digestibility, allows invertebrates that are capable of using them directly (or in an early phases of decomposition) to increase their biomass and abundance (Remy et al, 2017b). Moreover, this study demonstrates that resource increases induce diet modifications in some dominant macrofaunal herbivores, detritus feeders, and omnivores.…”
Section: Discussionmentioning
confidence: 71%
“…Mesocosm experiments showed that the input of a moderate amount of dead P. oceanica leaves had large and rapid effects on macrofauna community (i.e., changes in specific diversity and total and relative abundances) (Costa et al, 2019;Remy et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Duarte and Krause‐Jensen () pointed out as the potential sequestration of seagrass carbon exported beyond the meadows may approach 30% of the carbon sequestered within meadows. Detritus act as faunal magnets (Duggins et al, ; Remy, Gobert, & Lepoint, ), attracting fungi and bacteria, but also benthic invertebrates that use them as food and shelter (Heck et al, ; Remy, Mascart, De, Loïc, & Lepoint, ). Detritus undergoes decomposition and recycling that allows it to be channelled to higher trophic levels (Michel et al, ).…”
Section: Introductionmentioning
confidence: 99%